Стратегії розвитку туризму для України в умоваx військовиx дій та повоєнний період - Бондаренко, Валерій; Медведєва, Надія (Національний технічний університет "Харківський політехнічний інститут", 2023)
В статті досліджено сучасні особливості функціонування сфери туризму в Україні. Зазначено роль зовнішніх факторів у процесі забезпечення ефективного розвитку туристичної індустрії. Висвітлено основні фактори, що сприяли зростанню виїзного туризму на Україні: введення безвізового режиму з країнами ЄС, розширення авіаперевезень та відкриття прямих авіарейсів, зростання кількості пропозицій низькобюджетних турів, зростання купівельної спроможності українців, зміцнення курсу національної валюти. Але через карантинні обмеження закрилися аеропорти, спорожніли готелі, впав попит на послуги турагентств. І щойно сфера почала оговтуватися від коронавірусу, повномасштабне вторгнення рф в Україну знову завдало сильного удару туристичному бізнесу. Доведено, що важливою особливістю туристичного бізнесу є залежність від різких сезонних коливань попиту на туристичний продукт. Повномасштабне російське вторгнення негативно вплинуло на всі сфери економіки. Чи не найбільше постраждав український туристичний сектор. Закрите небо, обмеження на виїзд за кордон для чоловіків, вимушений переїзд чималої частини населення, безумовно, обмежили можливість подорожувати. В результаті негативного впливу зовнішніх факторів спостерігається падіння попиту на зовнішній туризм та готовність значної частки населення переорієнтуватися на споживання рекреаційних послуг на території України. За цих умов набуває особливої значущості дослідження питань, пов’язаних із підвищенням ефективності функціонування даної галузі, а також розширенням спектру та асортименту послуг, що надаються. Окремо слід зазначити зростання впливу розвитку туристичної галузі на характер соціально-економічних процесів в межах міських та сільських громад. Зростання попиту на зелений та етнічний туризм розкриває перед суб’єктами сімейного бізнесу широкі перспективи для розвитку, оскільки дані напрямки не потребують значних матеріальних затрат в якості стартового капіталу.

The article examines the current features of the tourism sector in Ukraine. The role of external factors in the process of ensuring the effective development of the tourism industry is noted. The author highlights the main factors that contributed to the growth of outbound tourism in Ukraine: the introduction of a visa-free regime with the EU countries, the expansion of air travel and the opening of direct flights, the growth of low-cost tours, the growth of purchasing power of Ukrainians, and the strengthening of the national currency. However, quarantine restrictions closed airports, emptied hotels, and reduced demand for travel agency services. And as soon as the industry began to recover from the coronavirus, Russia's full-scale invasion of Ukraine again dealt a severe blow to the travel business. It is proved that an important feature of the tourism business is its dependence on sharp seasonal fluctuations in demand for the tourism product. The research results show that outbound tourism in Ukraine has a pronounced seasonality. Further growth in demand for outbound tourism is noted, which in the future will ensure an even greater outflow of foreign currency, which will negatively affect the country's balance of payments and gross domestic product. The main trends in the context of the impact of the level of population income on the development of outbound tourism are identified. The full-scale Russian invasion has had a negative impact on all sectors of the economy. The Ukrainian tourism sector has suffered the most. The closed skies, restrictions on men traveling abroad, and the forced relocation of a large part of the population have certainly limited the ability to travel. As a result of the negative impact of external factors, there has been a drop in demand for foreign tourism and the willingness of a significant proportion of the population to reorient to the consumption of recreational services in Ukraine. Under these conditions, it is of particular importance to study issues related to improving the efficiency of this industry, as well as expanding the range and range of services provided. It is worth noting the growing impact of the tourism industry on the nature of socio-economic processes within urban and rural communities. The growing demand for green and ethnic tourism opens up broad prospects for development for family businesses, as these areas do not require significant material costs as stratum capital. At the same time, there is a question of the proper qualification level of persons planning to realize themselves in the hospitality business, and there is a need for proper organizational and informational support in this area. This, in turn, necessitates the optimization of the theoretical and methodological framework and methodological tools.
Strategies of tourism development for Ukraine in the conditions of military operations and the post-war period
Keywords: туризм; купівельна спроможність; гостиний бізнес; зелений туризм; виїзний туризм; конкурентоспроможність туристичної галузі; стратегічна програма розвитку; стратегія; туристичне підприємство; tourism; purchasing power; hospitality business; green tourism; outbound tourism; competitiveness of the tourism industry; strategic development program; strategy; tourism enterprise